The influence of appropriation of knowledge management system and intrinsic motivation on social capital in higher education institutions - Wan Maseri, Wan Mohd (2013)
As knowledge organization, Higher Education Institutions (HEI) are among the critical players in ensuring the knowledge being managed strategically in order to ensure the optimum benefits of knowledge creation, transfer and sharing happens among the internal and external community. These days, it was estimated that more than 80 percent of Knowledge Management (KM) programs end up with very low significant impact on the adopting organizations. Based on the existing studies, there are significant role of Appropriateness of KMS (A-KMS), Intrinsic Motivation (IM) and Social Capital (SC) in ensuring the KMS success. Thus, the purpose of this study was to empirically and systematically investigate the possible relationship between Appropriateness of KMS (A-KMS), Intrinsic Motivation (IM), Social Capital (SC) and demographic background in order to recommend the KMS Success Model. There were two phases of study using quantitative approach. The first phase was the survey approach where 1200 workers from Malaysian HEis were invited to participate in the survey and 398 (33%) was responded. Subsequently, the second phase was the semistructured interview where nine (9) senior managers from HEI were selected for detail interview. In quantitative study, a single mean t-test was conducted to identify whether the implementation level of A-KMS, IM and SC are significantly high. Furthermore, One-way ANOV A and independent sample t-tests were conducted to identify which demographic variables have influence on the SC. Subsequently a correlation and multiple regression analyses were conducted to identify the correlation and model that best represent the interrelation between A-KMS, IM, SC and demographic variables. A positive correlation was found between A-KMS and SC as well as IM and SC. As for multiple regression, the best model comprises of selected variables from A-KMS and IM was derived. The semi-structured interview was also conducted to complement and expand the findings from survey. Significant patterns and themes were identified and the findings suggest that the internal and external factors as well as barriers are the contextual factors that affect the implementation of A-KMS and IM to support the development of social capital. Finally, the Conceptual Framework of a A-KMS-IM-SC relationship was recommended accordingly.